MODEL DEVELOPMENT OF FITNESS FOR DUTY IN TRAIN DRIVERâS: STUDY ON OPERATION AREA I AND III - ADIASA, IKSAN
The development of fitness for duty models in train driver based on physical, mental and work characteristics is very important. The aims of the study are to develop fitness for duty models based on field studies using a Sustained Attention Test (SAT), Amylase Salivary Activity (SAA), Karolinska Sleepiness Scale (KSS) and Visual Analogue Scale (VAS). Thirty-two train drivers with 16 drivers for the morning shift (Jakarta - Cirebon route) and 16 drivers for the afternoon shift (Cirebon - Jakarta route) supported the study with age, height, weight, sleep length, sleep quality, shift, stress level, sleepiness, fatigue, sustained attention as independent variables and fitness for duty of train driver as the dependent variable. The results show that the assessment and evaluation of the fitness for duty level are quite good. Based on the models that have been made, there are 100% train drivers ready for duty. As much as 68.8% of train drivers are right predicted. But the value of adjusted R2 in the model is only 26.6%. SAT, SAA, and VAS have not been able to be used to fitness for duty of train drivers, while KSS can be utilized. Attention is very influential on fitness for duty for the afternoon shift. Changes in attention skills of train drivers are influenced by sleep. In addition, abilities are also needed by work shifts. Sleepiness and fatigue affect the fitness for duty. Fatigue affects the level of sleepiness of the driver. Sleepiness is affected by sleep and work shifts